A NOVEL SPECTROPHOTOMETRIC METHOD FOR DETERMINATION OF MODAFINIL IN PHARMACEUTICAL FORMULATIONS USING QUINALIZARIN - ISSA, BASHEER (Fırat Üniveristesi, 2017)
Analitik reaktif olarak Quinalizarin kullanılarak farmasötik formülasyonlar ve ilaçlarda modafinilin kantitatif tayini için basit ve ekstraksiyonsuz spektrofotometrik metod geliştirilmiş ve doğrulanmıştır. Quinalizarin ile modafinilin reaksiyonu metilalkol ortamında oda şartlarında 572 nm dalgaboyunda maksimum absorbans veren yük transfer kompleksi olan mavi renkli ürün oluşturulmuştur. Reaksiyonu etkileyecek farklı değişkenler optimize edilmiş ve çalışılmıştır. Optimize edilen deneysel şartlar altında Beer's kanunu 20-180 µg.mL-1 konsantrasyon aralığında, metod için tayin sınırı 0.258 µg.mL-1elde edilmiştir. Molar absorptivite metod için belirlenmiştir. Metod doğruluk hassaslık ve sağlamlık açısından doğrulanmıştır. Sonuçlar tatmin edicidir. Önerilen metod tablet formülasyonlarında bulunan modafinilin analizi için etkili bir şekilde uygulanabilir. Modafinilin geri kazanımı 99.9% olarak bulunmuştur. %RSD değeri bu medod için 0.6% değeri elde edilmiştir. Denemelerde tabletlerde bulunan diğer maddeler girişim yapmamıştır.

Simple, extraction free visible spectrophotometric method was developed and validated for the quantitative estimation of modafinil in pharmaceutical formulations and bulk drug using quinalizarin as analytical reagent. The method involve the reaction of modafinil with quinalizarin in alcoholic medium at room conditions to form a blue colored product exhibiting maximum absorption at 572 nm. Different variables affecting the reaction were studied and optimized. Under the optimized experimental conditions, Beer's law is obeyed in the concentration ranges of 20-180 ?g.mL?? with the detection of limit value of 0.258 ?g.mL?? for the method .The molar absorptivity for the method was reported. The method was validated in terms of accuracy, precision and robustness,the results were satisfactory. The proposed method was effectively applied to the analysis of the modafinil in their tablet formulations. Recovery studies for modafinil was found to be 99.9% . The %RSD value was found to be 0.6% for the method. The assay was not interfered by common excipients.
Quinalizarin kullanılarak farmasötik formülasyonlarda modafinilin tayini için yeni bir spektrofotometrik metod
Keywords: Kimya